Aplicación pedagógica del equipo Analizador de granos portátil “Food Tech” en procesos de transformación Agroindustriales. - Haro Santacruz, Luis Stalin (2022)
The portable grain analyzer "Food Tech" has the following characteristics, which are a digital screen, where it indicates the results, the grain analyzer is designed for research work, since it has a system, what analyzes automatically in less than a minute, it has a compartment, where is placed six AA batteries, it has a thermistor, what analyzes the dry grains, supports for thick and thin samples depending on the operator called cups need, this allows to make some functions, such as thick and thin grains analysis. Download data, through the previously installed software, it can be used to perform the following analyzes on coarse grains protein, moisture and fat and on fine grains protein, moisture. The operation manual consists of following points that are the ignition, calibration depends on the grain type to use (thick or thin), solution the most common errors, which occurs, when analysis, the steps to follow to get the analyzes, on the other hand, the maintenance manual consists of control records (preventive, corrective and routine), in order to extend the equipment useful life, the correct method of cleaning the equipment and safety measures for staff. In the made practices, they were got the following results, in thick and thin grains, in this case the barley bean according to the INEN and FAO standards accordance to the made analysis in the Agro-industrial Engineering Career meet all the established values in the humidity, fat and protein, which it must present before its industrialization.